ANALYSIS THE PERCENTAGE, CLINICAL, SUB CLINICAL FEATURES OF ACUTE ADRENAL INSUFFICIENCY AND EVALUATION OF TREATMENT RESULTS IN PATIENTS WITH SEPTIC SHOCK AT KIEN GIANG PROVINE IN 2022-2023 - Tran, Tan Dat; Ha, Van Phuc; Nguyen, Nhu Nghia (Cantho Journal of Medicine and Pharmacy, 2023)
Background: The incidence of adrenal insufficiency in the reflex ratio is quite high, and it increases the poor outcome in patients. Most clinical and laboratory features of adrenal insufficiency lack specificity for the disease reflex. Serum cortisol levels are useful tools for detecting and reflecting the significance of this condition. Objectives: To determine the rate of acute adrenal insufficiency and describe the clinical and subclinical features of septic shock patients with acute adrenal insufficiency in Kien Giang province in 2022-2023. Materials and methods: A crosssectional descriptive study was conducted on 62 patients >16 years old with septic shock and acute adrenal insufficiency at Kien Giang General Hospital from October 2022 to August 2023. Results: The NEWS score is significant in risk classification and predicting treatment outcome in patients with septic shock. 48% of patients with septic shock had acute adrenal insufficiency. Conclusion: Research results show that the rate of septic shock with acute renal failure in my study at Kien Giang General Hospital was 48%. The NEWS scale is significant in predicting early events.